Analysis of factors affecting employee performance at the government bureau of the regional secretariat of East Nusa Tenggara province - Jolanda Lisdawati Ndolu; Thomas Ola Langoday; Simon Sia Niha; Henny A. Manafe; Stanis Man (Institute of Computer Science (IOCS), 2023)
The urgency of the research is that there is a problem of employee competence at the Government Bureau of the Regional Secretariat of NTT Province, which based on the results of the assessment is stated to be lacking, so that the purpose of this study is to determine the description of employee performance, employee competence, work design, employee personality, work motivation, leadership, organizational culture, work environment, employee loyalty, employee commitment and work discipline at the Government Bureau of the Regional Secretariat of NTT Province in order to support the achievement of targets and work objectives that have been set. As well as analyzing the significance of variables that affect employee performance. This research uses quantitative methods. The research sample was employees at the Government Bureau of the Regional Secretariat of NTT Province, totaling 53 people. Data was collected by distributing questionnaires and analyzed using descriptive and inferential statistics using the SPSS application. Based on the results of this study, it can be contributed to the Government Bureau of the Regional Secretariat of East Nusa Tenggara Province to improve employee competence, work design, employee personality, work motivation, leadership, organizational culture, work environment, employee loyalty, employee commitment and work discipline in order to support the improvement of employee performance to a very good level.